Clopidogrel inhibits acetylcholine-induced contractions of urinary bladder in rat - Kacar, Emine; Serhatlioglu, İhsan (My University, 2019)
Aim: Clopidogrel as thrombocyte Adenosine Diphosphate (ADP) receptor antagonist is used especially in peripheric artery diseases by lengthening hemorrhage time, disrupting thrombocyte aggregation and decreasing blood viscosity. It shows its antagonist effects through glycoprotein (Gp) IIb/IIIa complex ADP by preventing its activation. Although the usage area and activity is in the vascular system, there are no adequate studies showing the activity of Clopidogrel on smooth muscle contraction-relaxation mechanism. This study was conducted to investigate the effects of Clopidogrel on bladder contraction-relaxation mechanism.Material and Methods: In the present study, the bladder tissues taken from Wistar-Albino (n=7) intact female rats were used. After the decapitation, the longitudinal bladder tissues that were received 1-mm-thick, 8-mm length, and 2-mm-width, were hung in the 5-ml isolated organ bath that had Krebs-Ringer bicarbonate solution by applying 1.5 gr strain. After the bladder contractions were induced with 10 ?M dose Acetylcholine (Ach), Clopidogrel was applied as two doses 0.1?M and 10?M in a noncumulative manner. The peak-to-peak (p-p) values and the values below the curve before and after the Clopidogrel application in the contraction induced with Ach were normalized as % change. The statistical analyses of the data were made in the SPSS 22.0 program by applying Paired T-Test. The p<0.05 value was accepted to be statistically significant.Results: When the bladder contractions induced with Ach and the values after Clopidogrel applications were compared, it was determined that there was 79% inhibition in the area values with Clopidogrel at 0.1?M dose; 87% at 10?M dose. In the p-p values, there was inhibition at 0.1?M dose with 63%, at 10?M dose with 64%, each of the two doses, the p-p and area values were found to be statically significant (P<0.001).Conclusions: Clopidogrel, which is used as an anti-aggregate especially in cardio-vascular diseases in clinical practice, has an inhibitory effect on bladder contraction (p-p and area), and the strongest inhibitor effect was observed at 10?M dose.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp